2016
DOI: 10.1371/journal.pone.0159818
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Colonization of Microborers at a Volcanically Acidified Coral Reef

Abstract: Experiments have demonstrated that ocean acidification (OA) conditions projected to occur by the end of the century will slow the calcification of numerous coral species and accelerate the biological erosion of reef habitats (bioerosion). Microborers, which bore holes less than 100 μm diameter, are one of the most pervasive agents of bioerosion and are present throughout all calcium carbonate substrates within the reef environment. The response of diverse reef functional groups to OA is known from real-world e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
2
24
1
Order By: Relevance
“…Measured depths of penetration in all substrates at the CO 2 venting areas in Ischia and Faial were particularly low (<30 μm after 6 months at Faial) and always lower than those found at ambient pH. Those depths, due mainly to Phaeophila sp., were similar to those reported by several authors for various carbonate substrates in warm temperate (Färber et al, 2015) and shallow tropical settings (Carreiro-Silva et al, 2009Enochs et al, 2016;Kiene et al, 1995;Mao Che et al, 1996). Phaeophila sp.…”
Section: Microboring Communities Under Naturally Acidified Waterssupporting
confidence: 91%
See 4 more Smart Citations
“…Measured depths of penetration in all substrates at the CO 2 venting areas in Ischia and Faial were particularly low (<30 μm after 6 months at Faial) and always lower than those found at ambient pH. Those depths, due mainly to Phaeophila sp., were similar to those reported by several authors for various carbonate substrates in warm temperate (Färber et al, 2015) and shallow tropical settings (Carreiro-Silva et al, 2009Enochs et al, 2016;Kiene et al, 1995;Mao Che et al, 1996). Phaeophila sp.…”
Section: Microboring Communities Under Naturally Acidified Waterssupporting
confidence: 91%
“…While several studies showed that an elevated pCO 2 with a pH of 7.9 increases rates of biogenic dissolution by at least 50% (Enochs et al, 2016;Reyes-Nivia et al, 2013;Tribollet et al, 2009), our data show the opposite trend. Rates of biogenic dissolution were indeed reduced by a factor 4 to 7 and 3 to 6 depending on sites and substrate types at the acidified sites at Ischia and Faial, respectively, compared to ambient pH sites.…”
Section: Contribution Of Biogenic Dissolution To Carbonate Total Weigcontrasting
confidence: 91%
See 3 more Smart Citations